The expressive lives of elders : folklore, art, and aging - Kay, Jon (Indiana University Press : Mathers Museum of World Cultures, Indiana University, 2018)
Can traditional arts improve an older adult's quality of life? Are arts interventions more effective when they align with an elder's cultural identity? In The Expressive Lives of Elders, Jon Kay and contributors from a diverse range of public institutions argue that such mediations work best when they are culturally, socially, and personally relevant to the participants. From quilting and canning to weaving and woodworking, this book explores the role of traditional arts and folklore in the lives of older adults in the United States, highlighting the critical importance of ethnographic studies of creative aging for both understanding the expressive lives of elders and for designing effective arts therapies and programs. Each case study in this volume demonstrates how folklore and traditional practices help elders maintain their health and wellness, providing a road map for initiatives to improve the lives and well-being of America's aging population.
Keywords: Art and older people.; Art therapy for older people.; Folk art -- Social aspects.; Decorative arts -- Social aspects.; Folklore -- Social aspects.; Identity (Psychology) in old age.; Older people.; Arts -- Therapeutic use.; Folklore.; Aging.; Quality of life.; Folklore; Aging; Quality of Life; Art et personnes âgées.; Art-thérapie pour personnes âgées.; Art populaire -- Aspect social.; Arts décoratifs -- Aspect social.; Folklore -- Aspect social.; Identité chez la personne âgée.; Personnes âgées.; Arts -- Emploi en thérapeutique.; Vieillissement.; Qualité de la vie.; elderly.; quality of life.; folklore (culture-related concept); SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; Identity (Psychology) in old age; Folklore -- Social aspects; Folk art -- Social aspects; Decorative arts -- Social aspects; Art therapy for older people; Art and older people; Arts -- Therapeutic use; Older people; Quality of life; Electronic books.